Superconvergence of nonconforming finite element approximation for the second order elliptic problem - Jasim, Rasool N.; Jari, Rabee H. (Journal of College of Education, 2021)
In this paper a general superconvergence of nonconforming finite element method for the second order elliptic problem is derived. In order to verify and support the theoretical results numerical examples are given.